2023
DOI: 10.3389/fnut.2023.1100422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium bicarbonate on the physicochemical properties of fermented rice flour and quality characteristics of fermented semi-dried rice noodles

Abstract: Considering the effect that fermentation can improve the quality of rice noodles, and given that fermented rice noodles usually have a significantly acidic taste that is not generally acceptable to consumers, this study aimed to neutralize or eliminate the acidic taste of fermented rice noodles by adding sodium bicarbonate, and improve the quality of fermented rice noodles. The physicochemical properties of fermented rice flour and quality characteristics of fermented semi-dried rice noodles were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Boiling also decomposes heat-sensitive antinutrients like trypsin inhibitors. In this study, results observed after boiling with NaHCO 3 could have occurred because increasing temperature via boiling in an alkaline solution, resulting from the anion hydrolysis of the HCO 3 – in NaHCO 3 results in the subsequent hydrolysis of proteins into smaller polypeptides, which makes them more accessible to digestive enzymes for breakdown and increases their nutritive value. …”
Section: Resultsmentioning
confidence: 86%
“…Boiling also decomposes heat-sensitive antinutrients like trypsin inhibitors. In this study, results observed after boiling with NaHCO 3 could have occurred because increasing temperature via boiling in an alkaline solution, resulting from the anion hydrolysis of the HCO 3 – in NaHCO 3 results in the subsequent hydrolysis of proteins into smaller polypeptides, which makes them more accessible to digestive enzymes for breakdown and increases their nutritive value. …”
Section: Resultsmentioning
confidence: 86%
“…Figure 2a shows that both guar gum and sodium bicarbonate had a negative effect on the whiteness of freeze‐dried taro balls. This may be due to the fact that guar gum itself is a white to light yellow‐brown free‐flowing powder, and as the addition of sodium bicarbonate increases, the flavonoid compounds in the raw material are released, resulting in a reduction in the whiteness of the product (Xiao et al ., 2023). This negative effect is reduced when both additives are added at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we found that fermented brown rice exhibited a superior water absorption rate than its unfermented counterpart, reducing its cooking time by 1.5 times [12]. The fermentation process induced surface cracks in the rice grains, facilitating moisture penetration during cooking and yielding a creamier texture [36].…”
Section: Enhancement Of Sensory and Textural Properties Of Processed ...mentioning
confidence: 97%